ANALISIS FAKTOR YANG MEMPENGARUHI TINGKAT KEPATUHAN TERHADAP PENGOBATAN TUBERKULOSIS - Sutiswa, Shandra Isasi; Fauzi, Ahmad Zil; Askur, Askur; Suryani, Maria Eka (Ensiklopedia of Journal, 2025)
Abstract: Based on preliminary studies conducted at the Pacar Keling Health Center from January to June 2023, 37 patients suffered from TB. The results of interviews with 5 respondents found that 3 people were compliant with treatment and 2 people were not compliant with treatment. The phenomenon obtained at the Pacar Keling Health Center is that there are still patients who are not compliant with TB treatment, including patients who drop out (incomplete treatment), repeat treatment, feel bored with long treatment. The purpose of the study was to analyze the factors that influence the level of adherence to tuberculosis treatment. The research design used in this study was cross sectional. The study was conducted in the working area of Pacar Keling Health Center. The study was conducted in August 2024. The study population was all patients registered at Pacar Keling Health Center as well as the research sample which amounted to 34 respondents. The sampling technique used total sampling. Data analysis was carried out univariate and bivariate. The results showed a relationship between motivation (p value: 0.004) and family support (p value: 0.000) to the level of compliance with tuberculosis treatment. It is recommended for the patient's family to always provide support and motivation to patients with tuberculosis in the treatment process and for the health center to provide counseling in the form of health promotion about TB disease that can be used by patients.Keywords: Adherence, Motivation, Tuberculosis